Concepções afirmativas e negativas sobre o ato de ensinar - Duarte, Newton [UNESP] (Centro de Estudos Educação e Sociedade (CEDES), 1998)
O artigo postula a necessidade de uma concepção afirmativa sobre o ato de ensinar e analisa criticamente algumas concepções consideradas negativas em relação ao ensino como transmissão de conhecimento. Nesse sentido, defende que a Escola Nova e o Construtivismo estabelecem uma dicotomia entre a transmissão de conhecimentos pelo professor e a conquista da autonomia intelectual pelo aluno, secundarizando, assim, o ensino e descaracterizando o papel do professor. O artigo analisa, ainda, alguns postulados defendidos por Vigotski e seguidores, que iriam numa direção oposta à das idéias defendidas pela Escola Nova e pelo Construtivismo.

The article postulates the necessity of an affirmative conception on teaching and critically analyses some conceptions considered negative according to teaching as transmission of knowledge. In this way, the article supports that the New School and Constructivism establish a dichotomy between the transmission of knowledge by the teacher and the effort for intellectual autonomy by the learner, leaving teaching in a secondary place and depriving the teachers role of its characteristics. The article still analyses some postulates defended by Vigotski and his followers, which read to an opposite direction, far from those ideas defended by the New School and Constructivism.
Affirmative and negative conceptions on teaching
Keywords: Ensino; construtivismo; Vigotski